Fadiga, capacidade funcional e qualidade de vida em pacientes com câncer durante o tratamento quimioterápico - Nunes, Graziana Oliveira (2020)
Introduction: According to the National Cancer Institute (INCA), the incidence of cancer has increased by 20% in the last decade and it is estimated that 600 thousand new cases will appear per year in 2018 and 2019. In addition, CA is considered the second main cause of death in the world, with treatment-related costs estimated at 150 billion dollars for 2020. Its dissemination in the body is a complex process and still not well established. The main treatment for cancer patients includes surgery, chemotherapy (QT), radiotherapy (RT). QT, one of the main treatment choices, is generally well tolerated by most patients, but it has many side effects, which significantly increase fatigue and reduce health-related functional capacity and quality of life. Objective: To investigate changes in fatigue, functional capacity and health-related quality of life in cancer patients. Method: Patients aged 35 to 70 years, diagnosed with cancer, who were attending the Chemotherapy Outpatient Clinic of the University Hospital of Santa Maria and the Infusion Center for Rheumatology and Oncology of the Hospital de Charity Doc. Astrogildo de Azevedo , by means of a sociodemographic questionnaire, quality of life (EORTC QLQ - C30), fatigue (FACT-F and EAF) and functional capacity (WHODAS), in addition to functional capacity tests (Senta-Levanta Test and 2-Hour Gait Test) minutes). Patients with venous thrombosis, lymphedema, plegia, lower limb paresis, who made testing difficult were excluded; with diagnosed cognition problems; who needed to interrupt chemotherapy treatment and those who self-reported rheumatological, musculoskeletal diseases, as well as lower limb trauma prior to surgery. The individuals answered the questionnaires before the first, second, third and fourth cycles of QT. The data were tabulated in the Microsoft Office Excel program and the Friedman test was used to compare the fatigue scores, functional capacity and quality of life between baseline and chemotherapy cycles. The Wilcoxon test was performed for post-hoc peer- o-peer comparison. In all tests, p≤0.05 was adopted. Statistical analyzes were performed using the SPSS 22.0 program. Results: Was evaluated 7 patients, most of them women, with breast cancer and the group was homogeneous in terms of sociodemographic data. Patients showed changes in functional capacity, both in the 2- inute stationary gait tests (p <0.002 and ES 1.409), in the sit-up (p <0.002 and ES 1.330), but this result was not observed in the evaluation of functionality (WHODAS). In the fatigue variable (FACT-F and EAF), no differences were found between any of the QT cycles. For variable HRQoL (EORTC QLQ C30), only the functional subscale showed a significant difference (p <0.009, ES 1.174), whereas the subscales of symptoms and global health did not show any difference. Conclusion: The findings allow us to infer that, for the sample evaluated, self-perceived quality of life and fatigue were not affected during chemotherapy, but functional capacity decreased significantly during the cycles.